# Yahoo Web Search

1. Sort by

1. ### Why can’t we write -a=b^x/y ?

x^2 = y  ...  y is a variable, not a constant like 4 ...  different rules apply   a^y = b^x     a = b^(x/y)  until you know a number value for b and y (which has become a root) we don 't know if the answer is pos, neg, or imaginary.

2 Answers · Education & Reference · 30/03/2020

2. ### Differential Equations Problem?

... + Fr = mh''.  Use the correct signs for the LHS terms. Fg is a constant [which one?]. Note that h'...

1 Answers · Science & Mathematics · 28/02/2020

3. ### (Boolean Algebra) Prove that xy + xy = (x+y)(x+y )?

LHS = xy + xy' = x(y + y') ..........distributive law = x(1) = x RHS = (x+y)(x+y' ) = x+(yy') ...........distributive law = x+(0) .............complement law = x LHS = RHS

1 Answers · Science & Mathematics · 03/08/2019

4. ### Rational Plus Irrational?

...x = c/d Then x = (c/d) - (a/b) RHS is clearly rational while LHS is irrational. This is a contradiction. Hence the sum must...

4 Answers · Science & Mathematics · 03/08/2019

5. ### Identical satellites X and Y of mass m are in circular orbits around a planet of mass M. The radius of the planet is R.?

... / R GmM / R = 2*KE and you should recognize the LHS as being equal to -GPE. If you find this helpful, please award...

1 Answers · Science & Mathematics · 07/05/2019

6. ### How to solve this differential eq problem?

... the given P(t) and showing that it equals the LHS. Or you can find the solution by solving the DE this way: ...

1 Answers · Science & Mathematics · 14/02/2019

7. ### CHEM HELP!!!?

....N. (oxidation number) of H on the LHS = O.N. of H on the RHS = +1...⁻ O.N. of H on the LHS = O.N. of H on the RHS, as...

3 Answers · Science & Mathematics · 16/02/2019

8. ### Can anyone solve it please?

...75707>pi-x>2.52611 {the principal values} Check: take x=0.609 LHS=ln[4-2(0.32723837...)]=1.20762311.. RHS=ln[3+0.32723837...]=1.20214264.. =>LHS...

3 Answers · Science & Mathematics · 12/02/2019

9. ### How do you solve this proof LTR? (Discrete Math)?

It is the distributive law, but you have to *prove* that by showing the LHS is a subset of the RHS and the RHS is a subset of the LHS and therefore LHS = RHS. Check the link below.

1 Answers · Science & Mathematics · 06/02/2019

10. ### If 5^(b-1) = 2, what is 5^(b+1)?

... by 5^2 each side to get 5^(b-1)*5^2 = 2 * 5^2. Simplify LHS to get 5^(b-1 + 2) = 2 * 5^2 5^(b+1) = 2 * 5^2 U can compute the ...

3 Answers · Science & Mathematics · 11/12/2018